Pengaruh Komitmen Organisasi dan Ketidakpastian Lingkungan terhadap Hubungan antara Partisipasi Anggaran dengan Senjangan Anggaran, - Hidayat, Hidayat; Suharsono, Judi (Akutansi Bisnis & Manajemen ( ABM ), 2007)
The issue of whether budget participation reduces slack has attracted the interest of many researchers. However, as indicates by Nouri and Parker (1996), studies examining the impact of participation on slack has not produced consistent results. Several studies found that participation reduced budget slack, while other found that participation increased budget slack. Adopting a contingency approach, this study argues that the effect of participation on budget slack is affected by other factors. In particular, this study examined the extent to which organizational commitment and environmental uncertainty moderated the relationship between participation and slack. It is hypothesized that, first participation reduces performance for individuals with high performance, and vice verse. Second, in situation of high uncertainty, participation reduces slack, but in situation of low uncertainty, participation increased slack. Based on response of 86 managers, the result show that emotions attachment, a dimension of organizational commitment, moderated the relationship between participation and slack